Ox cart accidents as a cause of spinal cord injury in Tanzania - Moshi, Haleluya I. (Spinal Cord Ser Cases, 2020)
STUDY DESIGN: Prospective Study. OBJECTIVES: To describe a unique site-specific injury mechanism for spinal cord injury: incidents involving ox-carts. SETTING: Main referral hospital for North-eastern Tanzania. METHODS: A prospective cohort study on Spinal Cord Injury (SCI) in a tertiary referral center in North-eastern Tanzania was examined for accidents related to the use of ox-carts, a major means of transport in a rugged rural area where the economy is largely based on agricultural practices. RESULTS: Five out of a total of 163 individuals admitted with SCI were injured in incidents directly related to the use of ox-carts. On admission each of the five individuals had different neurological level and corresponding injury severity as follows; C4 (American Spinal Injury Association Impairment Scale) AIS A), C5 (AIS D), C7 (AIS C), T1 (AIS C) and L1 (AIS D). Two out of the five patients developed secondary complications during their hospital stay. CONCLUSION: The nature of these injuries highlights the influence of one’s environment and social circumstances on the risk of sustaining a SCI. Such cases also serve to illustrate the need for tailored prevention, rehabilitation, and reintegration into society.